2020
DOI: 10.33448/rsd-v9i11.9992
|View full text |Cite
|
Sign up to set email alerts
|

Botanical studies, antimicrobial activity and cytotoxity of Eleutherine bulbosa (Mill.) Urb

Abstract: The use bulbs of Eleutherine bulbosa for treatament of diseases caused by malaria, amoeba and bacteria. This study accomplished the botanical and phytochemical characterization, antimicrobial activity and cytotoxic of E. bulbosa. For the anatomical studies, the studied material was fixed in formaldehyde – acetic acid and ethanol and it was dyed in safranin and in astra blue. For histochemistry, was fixed in buffered neutral formalin and in ferrous sulphate in formalina. Ethanolic Extract (EE) was submitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…From the ethanolic extract (EEEp; yield 2.84%) the following fractions were obtained: hexane (FHEp; yield 3.1%), dichloromethane (FDEp; yield 19.6%), ethyl acetate (FAEEp; yield 10.2%) and methanol (FMEp; 61.9% yield). Isoeleutherin was isolated from FDEp and its identification is described by Borges et al (2020) .…”
Section: Resultsmentioning
confidence: 99%
“…From the ethanolic extract (EEEp; yield 2.84%) the following fractions were obtained: hexane (FHEp; yield 3.1%), dichloromethane (FDEp; yield 19.6%), ethyl acetate (FAEEp; yield 10.2%) and methanol (FMEp; 61.9% yield). Isoeleutherin was isolated from FDEp and its identification is described by Borges et al (2020) .…”
Section: Resultsmentioning
confidence: 99%
“…After 48 h of treatment, isoeleutherin and FDMEp were more cytotoxic than the ethanol extract. The biological activities of E plicata have been attributed to quinonic compounds [ 26 , 27 , 47 ]. It is believed that it is an intrinsic property of these compounds associated with other structural factors, such as resonance effects, that may contribute to cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the microdilution test, the most promising sample was FDMEp (minimum inhibitory concentration = 125 μg/mL). For all samples, the Minimum Bactericidal Concentration was > 1000 μg/mL [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following compounds have already been isolated from this species: isoeleutherin ( Figure 1 A), eleutherin ( Figure 1 B), eleutherol ( Figure 1 C), eleutherinone ( Figure 1 D), (R)-4-Hydroxyeleutherine ( Figure 1 E), eleuthrone ( Figure 1 F), isoeleuthoside C ( Figure 1 G) and eleutherinol-8-O-b-D-glucoside ( Figure 1 H) [ 2 , 6 , 7 , 8 ]. Some studies demonstrated the activity of extracts, fractions and/or isolated substances from E. plicata against malaria parasites [ 7 ] and as antimicrobial [ 9 ] and antitumor agents [ 10 ]. Pharmacological activities have been related to quinone compounds, especially isoeleutherin [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%